At The Crossroads of Identity in Mohsin Hamid’s Novel Exit West (2017) - Asherly Randa; Leni Marlina (English Language and Literature, 2020)
This article is about the analysis of a novel Exit West (2017) by Mohsin Hamid. The problem of this analysis focuses on the issue of being at the crossroads of identity. The aim of analysis is to find out how far the characters Saeed and Nadia expose the issue of being at the crossroads of identity. This analysis involved fictional devices such as character, plot (conflict), and setting to reveal the issue of being at the crossroad of identity in the novel. The analysis deals with the concepts of hybridity by Homi K. Bhabha that is supported by the text and context based interpretation. The result of this analysis shows that the protagonists are a young man and a young woman who are faced with a condition that places them to be at their identity in being at the crossroads of identity. Thus, the character makes effort to assimilate and imitate to the new culture. These can be seen through their ways to blend with the society in attaining their identity.